Policy image resilience, multidimensionality, and policy image management: a study of US biofuel policy. (15th January 2014) - Mondou, Matthieu; Skogstad, Grace; Houle, David
Abstract This paper contributes to our understanding of why delegitimising focusing events, combined with the mobilisation of policy losers, does not always result in major policy change by undermining a monopolistic policy image and policy subsystem. Based on a close enquiry of American biofuel policy development, it argues that we can make headway in this endeavour by focusing on three factors: first, the congruence of a policy image with core values of the polity; second, the multidimensionality of a policy image; and third, policy image management strategies that maintain cohesion among coalition supporters and respond to outside criticism. In understanding better why some policy images (and policy monopolies) prove resilient when they come under assault, this paper offers a single case plausibility probe supported by indicative evidence from other policy studies.